2010
DOI: 10.1177/0363546510383479
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Situ Forces and Knee Kinematics in Anteromedial and High Anteromedial Bundle Augmentation for Partially Ruptured Anterior Cruciate Ligament

Abstract: Anatomic AM augmentation can lead to biomechanical advantages at time zero when compared with the nonanatomic (high AM) augmentation. Anatomic AM augmentation better restores the knee kinematics to the intact ACL state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 34 publications
2
61
0
Order By: Relevance
“…However, biomechanical tendencies in investigations with different loading magnitudes were often similar as ACLD increased ATT relative to ACL-intact knees throughout flexion under each Lachman’s and pivot-shift loads;[32, 62, 64, 66, 69, 96101] ACLR restored ATT relative to ACLD under Lachman’s loads, but not necessarily to the level of ACL-intact knees;[62, 96, 99, 101] ACLR restored ITR relative to ACL-intact knees under rotational loads;[31, 41, 62] and ACLR graft forces were not consistent with ACL-intact ligament forces. [6365, 99, 101] Therefore, normalized mechanical response of ACL, ACLD, and ACLR specimens generally remains constant across varied magnitudes of external loading, though absolute values may differ. Another limitation that was faced by this study was the definition of coordinate systems at the knee.…”
Section: Discussionmentioning
confidence: 99%
“…However, biomechanical tendencies in investigations with different loading magnitudes were often similar as ACLD increased ATT relative to ACL-intact knees throughout flexion under each Lachman’s and pivot-shift loads;[32, 62, 64, 66, 69, 96101] ACLR restored ATT relative to ACLD under Lachman’s loads, but not necessarily to the level of ACL-intact knees;[62, 96, 99, 101] ACLR restored ITR relative to ACL-intact knees under rotational loads;[31, 41, 62] and ACLR graft forces were not consistent with ACL-intact ligament forces. [6365, 99, 101] Therefore, normalized mechanical response of ACL, ACLD, and ACLR specimens generally remains constant across varied magnitudes of external loading, though absolute values may differ. Another limitation that was faced by this study was the definition of coordinate systems at the knee.…”
Section: Discussionmentioning
confidence: 99%
“…[112] Current techniques in ACLR over the past several years have focused on reproducing more anatomical tunnel placement and graft geometry to restore knee kinematics. [98] Xu et al[113] demonstrated in a cadaveric study that an anatomic anteromedial tunnel placement can lead to biomechanical advantages when compared to a non-anatomic placement, and the anatomic placement better restores knee kinematics to the native intact ACL state. [113] However, the anatomic placement had significantly greater in situ forces than the non-anatomic placement making it more vulnerable to graft failure.…”
Section: Functional Recovery Of the Kneementioning
confidence: 99%
“…[98] Xu et al[113] demonstrated in a cadaveric study that an anatomic anteromedial tunnel placement can lead to biomechanical advantages when compared to a non-anatomic placement, and the anatomic placement better restores knee kinematics to the native intact ACL state. [113] However, the anatomic placement had significantly greater in situ forces than the non-anatomic placement making it more vulnerable to graft failure. [113] Therefore, delaying a return to activity longer than the expected timeline may significantly help the recovering knee withstand the forces of returning to sport.…”
Section: Functional Recovery Of the Kneementioning
confidence: 99%
See 1 more Smart Citation
“…Subjects with femoral and tibia graft tunnels placed outside of the previously described native ACL footprints were included into the non-anatomic ACL group (Figure 1). [9,15,17] Based on previous studies [42,46], subjects with high AM tunnels were also included into the non-anatomic group (Figure 1). …”
Section: Methodsmentioning
confidence: 99%